Engaging veteran stakeholders to identify patient‐centred research priorities for optimizing implementation of lung cancer screening. (10th December 2021) - Yan, Alice; Hooyer, Katinka; Asan, Onur; Flower, Mark; Whittle, Jeff
Abstract: Background: Patient engagement in research agenda setting is increasingly being seen as a strategy to improve the responsiveness of healthcare to patient priorities. Implementation of low‐dose computed tomography (LDCT) screening for lung cancer is suboptimal, suggesting that research is needed. Objectives: This study aimed to describe an approach by which a Veteran patient group worked with other stakeholders to develop a research agenda for LDCT screening and to describe the research questions that they prioritized. Methods: We worked with Veterans organizations to identify 12 Veterans or family members at risk for or having experience with lung cancer to form a Patient Advisory Council (PAC). The PAC met repeatedly from June 2018 to December 2020, both independently and jointly, with stakeholders representing clinicians, health administrators and researchers to identify relevant research topics. The PAC prioritized these topics and then identified questions within these areas where research was needed using an iterative process. Finally, they ranked the importance of obtaining answers to these questions. Results: PAC members valued the co‐learning generated by interactions with stakeholders, but emphasized the importance of facilitation to avoid stakeholders dominating the discussion. The PAC prioritized three broad research areas—(1) the impact of insurance on uptake of LDCT; (2) how best to inform Veterans about LDCT; and (3) follow‐up and impact of screening results. Using these areas as guides, PAC members identified 20 specific questions, ranking as most important (1) innovative outreach methods, (2) the impact of screening on psychological health, and (3) the impact of outsourcing scans from VA to non‐VA providers on completion of recommended follow‐up of screening results. The latter two were not identified as high priority by the stakeholder group. Conclusions: We present an approach that facilitates co‐learning between Veteran patients and providers, researchers and health system administrators to increase patient confidence in their ability to contribute important information to a research agenda. The research questions prioritized by the Veterans who participated in this project illustrate that for this new screening technology, patients are concerned about the practical details of implementation (e.g., follow‐up) and the technology's impact on quality of life. Patient or Public Contribution: Veterans and Veteran advocates contributed to our research team throughout the entire research process, including conceiving and co‐authoring this manuscript.